(untitled) (Journal of Dentistry and Allied Science, 2024)
Background: Trigeminal neuralgia (TNg) is considered as one of the most severe painful disorders in the orofacial region. Anticonvulsants are most commonly used for such pain management. Carbamazepine is considered as first line of drug for the pain management of TNg. But, a new medicine namely, oxcarbazepine, that is a keto derivative of Carbamazepine, recently caught attention for its promising effect as an anti-convulsant drugs. However, little is known about its effect and safety in TNg management in aspects of Bangladeshi patients. Here, in this study we aim to compare the effectiveness and tolerability of carbamazepine versus oxcarbazepine in the pain management of TNg. Methods: People Patient with TNg were identified while visiting Bangabandhu Sheikh Mujib Medical University for treatment purpose. Thirty patients with TNg were selected irrespective of age, gender, religion or socioeconomic status of the patients, and selection criteria. Patients were administrated with oxcarbazepine (group A) and carbamazepine (group B) for certain time, and data were collected during indicated follow up. Results: In this study, 53.3 % patients were found within 51-60 years age group, followed by (46.7%) were in the age group of 40-50. It was reported that 43.3% were male and 56.7% patients were female. In present study, pain was significantly reduced in group A compared to group B (p <0.001). The mean pain score in group B was 4.11+0.91, but promisingly in group A was 1.41+ 0.78. Although, after one month of treatment, we found adverse effects in 4 (26.7%) patients in group A and 9 (60.0%) patients in group B. However, after 6 months of treatment no side effect was observed in group A, but 11 (73.3%) patients had side effect in group B. Side effects were significantly decreased in group A after 3 and 6 months compared to group B (p<0.05). Conclusion: The significant analgesic effects of oxcarbazepine and its generally improved safety and tolerability profile compared to carbamazepine, suggest that oxcarbazepine will be an important addition to TNg pain management. Journal of Dentistry and Allied Science, Vol. 7 No 1: 35-44